Approaches for Recognition of a New Occupation as a Liberal Profession in Romania - Haţegan, Vasile (B@belonline, 2024)
The paper aims to present the current state and perspectives regarding the path of philosophical practice towards recognition as a liberal profession in Romania, starting from the existing concepts about liberal profession. The legal aspects of the legal regulation of a profession of this kind are the premises that fully highlight the characteristics of philosophical counseling, a new specialization promoted by Romanian universities. The context thus created led to concrete actions of the new practitioners of philosophy, which manifest themselves in society in the form of new specialists trained in philosophical counseling, being the first steps towards recognizing the new occupation thus defined, with perspectives of standardization and regulation as a distinct profession, as part of the liberal professions, already present on the labor market. Some conclusions are included regarding the need for a new profession, distinct from the occupation of philosopher, generated by the specialization tendency of the philosophical practice and defining a new profession, so necessary for persons and human communities.